Institutional barriers to actionable science: Perspectives from decision support tool creators. Issue 128 (February 2022) - Pearman, Olivia; Cravens, Amanda E.
Abstract: Scholars have identified a 'usability gap' between science and its ability to inform real-world decisions as well as a range of factors that facilitate or impede attempts to span the usability gap with information products. However, most attention has focused on barriers related to information users; much less research focuses on the unique institutional and organizational barriers experienced by creators of decision support tools. To address this gap, we used semi-structured interviews to investigate the perspectives and experiences of practitioners holding scientific or technology roles, including their goals for their tools, their perceptions of success in meeting those goals, and the barriers and opportunities they encountered. We find that there is often a mismatch between what tool creators know is necessary to achieve success for their tools and what is actually possible given various constraints. Our results suggest that knowledge may be a less important barrier to conducting actionable science through creating decision support tools than the institutional context in which tool creators work. Highlights: Creators of decision support tools (DSTs) understand actionable science concepts. These DST creators value stakeholder engagement throughout the tool design process. Institutional barriers keep tool creators from working in ways they would like.